A Novel Mutation of GDAP1 Associated with Charcot-Marie-Tooth Disease in An Iranian Family - MOHAMMADI PARGOO, Esmaeel; ARYANI, Omid; TONEKABONI, Seyyed Hassan; KAMALIDEHGHAN, Behnam; HOUSHMAND, Massoud (Iranian Journal of Child Neurology, 2012)
As a result of higher distributed consanguinity in the Mediterranean region and the Middle East, autosomal-recessive forms of Charcot-Marie-Tooth (ARCMT) are more common in these areas. CMT disease caused by mutations in the ganglioside-induced differentiation-associated protein 1 (GDAP1) gene is a severe autosomal recessive neuropathy resulting in either demyelinating CMT4A neuropathy or axonal neuropathy with vocal cord paresis. The patient was an 8-year-old boy with AR inheritance that showed some delayed achievement of motor milestones, including walking, also bilateral foot drop, wasting of distal muscles in the legs, pes cavus and marked weakness of the foot dorsiflexors. He had no hoarseness or vocal cord paralysis. Total genomic DNA was extracted from whole peripheral blood of the patient and his family by using standard procedures. PCR- sequencing method were used to analysis the whole coding regions of the GDAP1 gene. A novel homozygote insertion of T nucleotide in codon 34 was detected (c.100_101insT) that probably led to an early stop codon. This mutation may be associated with a common haplotype, suggesting a common ancestor that needs further investigation in the Iranian population.